Epidemiology and pathophysiology of adulthood-onset thrombotic microangiopathy with severe ADAMTS13 deficiency (thrombotic thrombocytopenic purpura): a cross-sectional analysis of the French national registry for thrombotic microangiopathy. Issue 5 (May 2016) - Mariotte, Eric; Azoulay, Elie; Galicier, Lionel; Rondeau, Eric; Zouiti, Fouzia; Boisseau, Pierre; Poullin, Pascale; de Maistre, Emmanuel; Provôt, François; Delmas, Yahsou; Perez, Pierre; Benhamou, Ygal; et al.
Summary: Background: Thrombotic thrombocytopenic purpura is a thrombotic microangiopathy related to a severe deficiency of ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type 1 repeats, member 13; activity <10%). We aimed to investigate the association between mechanisms for ADAMTS13 deficiency and the epidemiology and pathophysiology of thrombotic thrombocytopenic purpura at initial presentation. Methods: Between Jan 1, 1999, and Dec 31, 2013, we did a cross-sectional analysis of the French national registry for thrombotic microangiopathy to identify all patients with adult-onset thrombotic microangiopathy (first episode after age 18 years) who had severe ADAMTS13 deficiency at presentation. ADAMTS13 activity, anti-ADAMTS13 IgG, and ADAMTS13 gene mutations were investigated by a central laboratory. We collected patients' clinical data for correlation with their ADAMTS13 phenotype and genotype. We used logistic regression analysis to identify variables significantly associated with idiopathic thrombotic thrombocytopenic purpura, as measured by estimated odds ratios (ORs) and 95% CIs. This study is registered withClinicalTrials.gov, numberNCT00426686 . Findings: We enrolled 939 patients with adult-onset thrombotic thrombocytopenic purpura, of whom 772 (82%) patients had available data and samples at presentation and comprised the cohort of interest. The prevalence of thrombotic thrombocytopenic purpura in France was 13 cases per million people. At presentation, 378 (49%) patients had idiopathic thrombotic thrombocytopenic purpura, whereas 394 (51%) patients had disease associated with miscellaneous clinical situations (infections, autoimmunity, pregnancy, cancer, organ transplantation, and drugs). Pathophysiologically, three distinct forms of thrombotic thrombocytopenic purpura were observed: 585 (75%) patients had autoimmune disease with anti-ADAMTS13 IgG, 166 (22%) patients had acquired disease of unknown cause and 21 (3%) patients had inherited disease (Upshaw-Schulman syndrome) with mutations of the ADAMTS13 gene. Idiopathic thrombotic thrombocytopenic purpura were mainly autoimmune (345 [91%] cases), whereas non-idiopathic diseases were heterogeneous, including a high rate of unexplained mechanisms for ADAMTS13 deficiency (133 [34%] cases). Obstetrical thrombotic thrombocytopenic purpura cases (n=62) were specifically remarkable because of the high rate of patients with Upshaw-Schulman syndrome (21 [34%] patients). Interpretation: Our study shows that thrombotic thrombocytopenic purpura is a heterogeneous syndrome, and that features of the disease at presentation are strongly associated with the mechanisms of ADAMTS13 deficiency. In addition to mechanistic insight, our findings could have implications for the initial therapeutic management of patients with this disorder. Funding: Assistance Publique-Hôpitaux de Paris.